Shopping and surveillance: the politics of everyday life in socialism - Luthar, Breda (Javnost-The Public, 2004)
Among the strongest individual memories of life in state-socialism was the lack of desired goods, the culture of shortages, and the “dictatorship” over needs. With the gradual opening of the border between Italy and Yugoslavia after 1955, shopping trips to Italy became regular social events and cultural phenomena. The article analyzes the formal properties of the cultural and communicative practices of “going shopping to Trieste” and draws on personal memories of former shoppers. It explores social experiences of a culture of shortages, the symbolic value and public meaning of goods, the system of interaction between border officials and shoppers/smugglers, gender divisions, and ethnic and class differentiation involved in shopping expeditions. The article treats everyday life as a critical arena for the communicative construction, reproduction and transformation of power, and elaborates on resistance strategies as a metaphor for power relations and surveillance at the level of everyday life in socialism.